2010
DOI: 10.1371/journal.pone.0013566
|View full text |Cite
|
Sign up to set email alerts
|

5-Androstene-3β,7β,17β-triol (β-AET) Slows Thermal Injury Induced Osteopenia in Mice: Relation to Aging and Osteoporosis

Abstract: 5-androstene-3β,7β,17β-triol (β-AET), an active metabolite of dehydroepiandrosterone (DHEA), reversed glucocorticoid (GC)-induced suppression of IL-6, IL-8 and osteoprotegerin production by human osteoblast-like MG-63 cells and promoted osteoblast differentiation of human mesenchymal stem cells (MSCs). In a murine thermal injury model that includes glucocorticoid-induced osteopenia, β-AET significantly (p<0.05) preserved bone mineral content, restored whole body bone mineral content and endochondral growth, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The results suggest that DHEA significantly decreased viability and increased osteo‐induction of MSCs. Previous research has also shown that androstenetriol, an active metabolite of DHEA, promoted osteoblast differentiation of MSCs (Malik et al ., ). The promoted osteogenesis was particularly clear with osteo‐induced MSCs.…”
Section: Discussionmentioning
confidence: 97%
“…The results suggest that DHEA significantly decreased viability and increased osteo‐induction of MSCs. Previous research has also shown that androstenetriol, an active metabolite of DHEA, promoted osteoblast differentiation of MSCs (Malik et al ., ). The promoted osteogenesis was particularly clear with osteo‐induced MSCs.…”
Section: Discussionmentioning
confidence: 97%
“…␤AET is one of several DHEA metabolites with anti-inflammatory activity [29,45], noting that some of these metabolites are also susceptible to metabolism, and therefore may be further transformed in vivo into the active entities. Recent studies suggest natural roles for ␤AET in preserving bone mineral content [46] and preventing the development of metabolic syndrome [35]. In a placebo controlled clinical trial it was shown to lower cholesterol in normal human subjects [47] consistent with DHEA activity in dogs reported by MacEwen and Kurzman [48].…”
Section: Discussionmentioning
confidence: 66%
“…Accordingly findings with this pharmaceutical may define the roles of ␤AET, a natural component of the human metabolome. In addition to a role in stem cell fate decisions [71], it is involved in metabolic processes, and possesses immune modulation properties that were previously shown to temper autoimmune disease in murine models and shown here to inhibit the acute inflammatory response and resolve immune senescence in aged mice. However, ␤AET's metabolic lability and limited bioavailability preclude its use as a practical treatment for acute inflammation, whereas the pharmacology of 17␣-alkynyl-␤AET is suitable for with this application.…”
Section: Discussionmentioning
confidence: 82%
“…Another related steroid, 5-androstene-3β,7β,17βtriol, exhibits glucocorticoid-opposing and immunemodulating activity (Ahlem et al 2011), and because its plasma levels positively correlate with BMI in healthy men and women, the authors suggested its compensatory role in preventing the development of metabolic syndrome (Auci et al 2011). 5-androstene-3β,7β,17βtriol (β-AET), an active metabolite of dehydroepiandrosterone (DHEA), reversed the glucocorticoid induced suppression of IL-6, IL-8 and osteoprotegerin production (Malik et al 2010). This steroid also influences estrogen receptor beta signaling (Pettersson et al 2010).…”
Section: Other Effects Of 7-oh-dheamentioning
confidence: 99%